Az egerek népétől a geometriai progresszióig: Kafka és Mészöly - Lénárt, Tamás (Studia Litteraria, 2023)
The paper analyses Franz Kafka’s Josephine the Singer, or the Mouse Folk and Miklós Mészöly’s A Report On Five Mice, examining the modulations of the traditional genre of the animal fable in both works, and its relation to the narratological structure and the narrative language of the texts, seeking an answer to the question of how non-human existence can be expressed in human language.